Komagataeibacter rhaeticus as an alternative bacteria for cellulose production - Machado, Rachel T.A.; Gutierrez, Junkal; Tercjak, Agnieszka; Trovatti, Eliane; Uahib, Fernanda G.M.; Moreno, Gabriela de Padua; Nascimento, Andresa P.; Berreta, Andresa A.; Ribeiro, Sidney J.L. [UNESP]; Barud, Hernane S. [UNESP] (Elsevier, 2016)
A strain isolated from Kombucha tea was isolated and used as an alternative bacterium for the biosynthesis of bacterial cellulose (BC). In this study, BC generated by this novel bacterium was compared to Gluconacetobacter xylinus biosynthesized BC. Kinetic studies reveal that Komagataeibacter rhaeticus was a viable bacterium to produce BC according to yield, thickness and water holding capacity data. Physicochemical properties of BC membranes were investigated by UV–vis and Fourier transform infrared spectroscopies (FTIR), thermogravimetrical analysis (TGA) and X-ray diffraction (XRD). Additionally, scanning electron microscopy (SEM) and atomic force microscopy (AFM) were also used for morphological characterization. Mechanical properties at nano and macroscale were studied employing PeakForce quantitative nanomechanical property mapping (QNM) and dynamic mechanical analyzer (DMA), respectively. Results confirmed that BC membrane biosynthesized by Komagataeibacter rhaeticus had similar physicochemical, morphological and mechanical properties than BC membrane produced by Gluconacetobacter xylinus and can be widely used for the same applications.
Keywords: 3D network structure; Bacterial cellulose; Cellulose production; Komagataeibacter rhaeticus; Mechanical properties